Alternative pedicle screw design via biomechanical evaluation - Kwon, Jiwoon; Ha, Myung Heon; Lee, Moon Gu (Applied Sciences (Switzerland), 2020)
With the recent increase in the elderly population, many people suffer from spinal diseases, and, accordingly, spinal fusion surgery using pedicle screws has been widely applied to treat them. However, most research on pedicle screw design has been focused on the test results rather than the behavior of the screws and vertebrae. In this study, a design platform with a series of biomechanical tests and analyses were presented for pedicle screw improvement and evaluation. The platform was then applied to an alternative hybrid screw design with quadruple and double threads. An experimental apparatus was developed to investigate the bending strength of the screw, and several tests were performed based on the ASTM F1717 standard. In the experiments, it was confirmed that the alternative pedicle screw has the highest bending strength. To examine the stress distribution of pedicle screws, finite element models were established, through which it was found that the proposed pedicle screw has sufficient mechanical safety to make it acceptable for spinal fusion treatment. Finally, we conclude that the platform has good potential for the design and evaluation of pedicle screws, and the alternative dual screw design is one of the best options for spinal fusion surgery.
Keywords: Lumbar spine; Pedicle screw; Pull-out strength; Spinal fusion; Surgical convenience